Surface-functionalizable amphiphilic nanoparticles for pickering emulsions with designer fluid–fluid interfaces. Issue 46 (21st April 2016) - Pan, Ming; Kim, Minkyu; Blauch, Lucas; Tang, Sindy K. Y.
Abstract : This work describes the synthesis of amphiphilic silica nanoparticles with functionalizable surfaces for stabilizing aqueous drops in fluorinated oils, and for enabling the generation of emulsions with tailored interfacial properties. Abstract : This work describes the synthesis of amphiphilic silica nanoparticles with functionalizable surfaces for the stabilization of aqueous drops in fluorinated solvents. State-of-the-art droplet microfluidics technology has relied on a single type of surfactant consisting of perfluorinated polyether and polyethylene glycol (PFPE–PEG). This type of surfactant, however, is known to have limitations including synthetic complexity and the cross-contaminations of droplet content caused by the inter-drop transport of small hydrophobic molecules. Previously we have overcome these limitations by replacing the surfactant with partially fluorinated silica nanoparticles (referred to as "F-SiO2 NPs") as droplet stabilizers. Nonetheless, neither surfactants nor F-SiO2 NPs can provide additional functionalities at fluid–fluid interfaces due to the lack of reactive functional groups for further modifications. Here we introduce reactive groups on the surface of F-SiO2 NPs by the co-hydrolysis of different silane precursors, and demonstrate the successful conjugation of particle surfaces with fluorescent molecules, biomolecules and polymers. Our particles serve dual functions: they are amphiphilic for stabilizing water-in-oil drops, and they possess functional surface groups for presenting desired surface chemistries at the droplet interface. These particles offer the following advantages: (1) their synthesis is simple and scalable (up to grams); (2) they are effective in stabilizing droplets against coalescence under typical droplet manipulation conditions; (3) they prevent inter-drop molecular transport; and (4) their surfaces contain reactive groups such as amines that are capable of further conjugation with various "designer" molecules. We believe that the particles described in this work will open up opportunities in creating emulsions with tailored interfacial properties for new applications requiring customized fluid–fluid interfaces.